Convergence To Approximate Solutions of Multivalued Operators - Maibed, Zena Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The goal of this study is to provide a new explicit iterative process method approach for solving maximal monotone(M.M )operators in Hilbert spaces utilizing a finite family of different types of mappings as( nonexpansive mappings,resolvent mappings and projection mappings. The findings given in this research strengthen and extend key previous findings in the literature. Then, utilizing various structural conditions in Hilbert space and variational inequality problems, we examine the strong convergence to nearest point projection for these explicit iterative process methods Under the presence of two important conditions for convergence, namely closure and convexity. The findings reported in this research strengthen and extend key previous findings from the literature